2012
DOI: 10.3390/biology1030521
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of HIV-1 Reverse Transcriptase—Associated Ribonuclease H Activity

Abstract: HIV-1 enzyme reverse transcriptase (RT) is a major target for antiviral drug development, with over half of current FDA-approved therapeutics against HIV infection targeting the DNA polymerase activity of this enzyme. HIV-1 RT is a multifunctional enzyme that has RNA and DNA dependent polymerase activity, along with ribonuclease H (RNase H) activity. The latter is responsible for degradation of the viral genomic RNA template during first strand DNA synthesis to allow completion of reverse transcription and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 52 publications
1
49
0
Order By: Relevance
“…The potential role of the interplay of reverse transcription and uncoating has been recently suggested to provide an enclosed environment facilitating firststrand transfer during HIV-1 reverse transcription (29). With the easy adaptability of our live-imaging fluorescence HIV-iGFP system, we tested this possibility in the transient presence of 7390, an RNase H activity inhibitor specific to HIV-1 reverse transcription (47) (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential role of the interplay of reverse transcription and uncoating has been recently suggested to provide an enclosed environment facilitating firststrand transfer during HIV-1 reverse transcription (29). With the easy adaptability of our live-imaging fluorescence HIV-iGFP system, we tested this possibility in the transient presence of 7390, an RNase H activity inhibitor specific to HIV-1 reverse transcription (47) (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%
“…CsA was used at 5 μM; NVP was obtained from the NIH repository of the NIH AIDS Reagent Program, Division of AIDS, National Institute of Allergy and Infectious Diseases, NIH, and used at 10 μM (dissolved in water according to NIH AIDS Reagent Program solubility limit); MG132 was used at 1 μg/mL; Polybrene was used at 10 μg/mL; Oxyfluor/OxyRase was used at a 1:200 dilution; DL-lactate was used at 15 mM; and RnaseH inhibitor 7390 (shown as 8b in ref. 47) was used at 10 μM for live imaging and CsA washout experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIV RNase H and integrase have attracted much attention as potential drug targets, with hundreds of compounds being reported to inhibit these enzymes (43,44). Most of the inhibitors bind at the active site via interactions with the divalent cations (45)(46)(47)(48).…”
mentioning
confidence: 99%
“…Such compounds act by chelating the two metal cofactors that are coordinated to the catalytic RNH active site residues (14)(15)(16)(17)(18). The HPDs chosen for this study (see Table S1 in the supplemental material) were previously reported to potently inhibit HIV-1 RNH activity (18) and thus were appealing candidates for HBV RNH screening.…”
mentioning
confidence: 99%